Unlocking the Potential of Buckwheat Hulls, Sprouts, and Extracts: Innovative Food Product Development, Bioactive Compounds, and Health Benefits – a Review - Zhibek Atambayeva; Almagul Nurgazezova; Kumarbek Amirkhanov; Zhanna Assirzhanova; Altyngul Khaimuldinova; Haykuhi Charchoghlyan; Meruyert Kaygusuz (Polish Journal of Food and Nutrition Sciences)
This comprehensive review explores the underutilized buckwheat hulls, sprouts, and grain and sprout extracts, concentrating on their nutritional characteristics, health advantages, and possible uses in developing functional food products. Buckwheat, a pseudocereal, is emphasized for its impressive nutritional content, including high levels of dietary fiber, essential minerals, and vitamins, as well as bioactive compound content, such as phenolic acids and flavonoids mainly rutin. The paper discusses the significant antioxidant and antimicrobial properties of buckwheat hulls, sprouts, and extracts, which contribute to their utility in creating healthier, functional food products. Buckwheat sprouts are noted for their enhanced levels of antioxidants and nutrients compared to mature grains. Meanwhile, buckwheat hulls, traditionally seen as by-products, are identified as sources of dietary fiber and flavonoids, suitable for use in dietary supplements and functional foods. The extracts from these parts are rich in bioactive compounds that offer health-promoting effects. The possible effects of addition of buckwheat hulls, sprouts, and extracts to food products in terms of nutritional, textural, and sensory properties are also discussed. The review underscores the need for further research to optimize the use of buckwheat less-utilized parts and to better understand their health impacts. By highlighting the novel uses and health benefits of buckwheat hulls, sprouts, and extracts, the review contributes to the growing field of sustainable food practices and the development of functional foods.